Crafts, affections and wisdoms: - Juliana Aquino Machado; Gilberto Ferreira da Silva (Revista Diálogo Educacional)
This study aims to evaluate an experience of continuing education with basic education teachers developed in a Municipal Education Network (RME), during the years 2017 to 2020. Qualifying education, especially Basic Education, necessarily involves the relations established with the University, given the important role it plays in the training, both initial and continuing, of teachers. The study is based on records produced during the training experience and produces the analysis inspired by six researcher postures: a) Access, b) Sensitize (-se), c) Contemplate / Listen, d) Talk / Dialog, e) Reflect / Reflect, f) Record / Document / Systematize. As a result, the following questions are located: the exercise of attentive and committed listening of educators was instituted as a methodology that gained other spaces, becoming part of the culture of the network, enabling a constant self-formative process; the intellectual protagonism as an epistemic claim of the knowledge produced in the exercise of daily teaching; the feeling of belonging to a work project that was built in the collective, made possible by creating training spaces where one learns to learn and learns to teach; the value of the act of researching and learning to make use of what science bequeaths as heritage, in the field of literature on teacher education, served as guidance to advance in the training work.